Evaluation of a Multifaceted Protocol in Reducing Unnecessary Telemetry Monitoring across a Large Healthcare System. Issue 12 (December 2022) - Patidar, Viniya; Park, Jung Mi; Khasnavis, Tanya; Baker, Dylan; Leong, Traci; Crichlow, Vena; Hunt, Daniel P.; O'Donnell, Christopher
Abstract : This article describes the advent of a multifaceted electronic telemetry protocol aimed at curbing unnecessary telemetry utilization across a large healthcare network. We developed a two-step approach by first hardwiring the American Heart Association guidelines for appropriate telemetry use within the electronic ordering system, and second by using an electronic nursing discontinuation task form to remove patients from telemetry when it is no longer recommended. Our results showed a substantial improvement in the reduction of unnecessary telemetry monitoring in hospitalized patients with an associated cost avoidance. Abstract: Objectives: Telemetry is frequently overused in hospitals. The goal of this study was to evaluate a telemetry protocol aimed at decreasing inappropriate telemetry utilization across four different hospitals within a large healthcare system by modifying the electronic telemetry order to incorporate the 2017 American Heart Association practice guidelines on the appropriate use of telemetry and using an electronic nursing screening task form to safely discontinue telemetry. Methods: We performed a retrospective analysis of telemetry utilization before and after we implemented a protocol across four hospitals within a large healthcare system. We compared the average number of days of telemetry monitoring and hospital length of stay during the preintervention period with the 6-month postintervention period. Results: There were a total of 23, 774 encounters evaluated. There was a statistically and clinically significant 24% decrease in telemetry duration between pre- and postintervention time periods ( P < 0.0001). The mean (standard error) telemetry duration was 4.11 (0.17) and 2.36 (0.13) days in pre- and postintervention periods, respectively. Conclusions: The results of our study demonstrate a statistically significant decrease in overall duration of telemetry monitoring by nearly 1.75 days across each of the four hospitals with the implementation of a multifaceted telemetry protocol that included hardwiring the American Heart Association practice guidelines into the electronic order and using a nursing-driven discontinuation protocol.